Influence of Interference between Vertical and Roll Vibrations on the Dynamic Behaviour of the Railway Bogie - Mădălina Dumitriu; Ioana Izabela Apostol (Vibration, 2022)
This paper investigates the dynamic behaviour of a two-axle bogie under the influence of interference between the vertical vibrations of bounce and pitch—generated by the track irregularities—and the roll horizontal vibrations—excited by the asymmetry in the suspension damping that can be caused by the failure of a damper during exploitation. For this purpose, the results of numerical simulations are being used, as developed on the basis of two original models of the bogie-track system, namely the model of the bogie with symmetrical damping of the suspension—track and the model of the bogie with asymmetrical damping of the suspension—track, respectively. The dynamic behaviour of the bogie with symmetrical/asymmetrical damping is evaluated in five reference points of the bogie regime of vibrations, based on the Root Mean Square of acceleration (RMS acceleration). The results thus obtained highlight the characteristics regarding the symmetry/asymmetry of the regime of vibrations in the bogie reference points and the location of the critical point of the bogie regime of vibrations. The influence of the suspension asymmetry upon the dynamic behaviour of the bogie is analysed in an original manner, hence leading to conclusions that might establish themselves as the starting point of a new fault detection method of the dampers in the primary suspension of the railway vehicle.